2007
DOI: 10.1086/510063
|View full text |Cite
|
Sign up to set email alerts
|

First High‐Contrast Science with an Integral Field Spectrograph: The Substellar Companion to GQ Lupi

Abstract: We present commissioning data from the OSIRIS integral field spectrograph (IFS) on the Keck II 10 m telescope that demonstrate the utility of adaptive optics IFS spectroscopy in studying faint close-in sub-stellar companions in the haloes of bright stars. Our R≈2000 J-and H-band spectra of the sub-stellar companion to the 1-10 Myr-old GQ Lup complement existing K-band spectra and photometry, and improve on the original estimate of its spectral type. We find that GQ Lup B is somewhat hotter (M6-L0) than reporte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 56 publications
(115 reference statements)
5
50
0
Order By: Relevance
“…There are several caveats about these accreting companions that are worth noting. Paβ emission was not observed in the moderate-resolution spectroscopy of GQ Lup B presented by McElwain et al (2007) and Lavigne et al (2009), which suggests that the emission observed by Seifahrt et al (2007) was variable. Similarly, Wolff et al (2017) also found variable emission for DH Tau B.…”
Section: How Common Is Paβ Emission?mentioning
confidence: 82%
“…There are several caveats about these accreting companions that are worth noting. Paβ emission was not observed in the moderate-resolution spectroscopy of GQ Lup B presented by McElwain et al (2007) and Lavigne et al (2009), which suggests that the emission observed by Seifahrt et al (2007) was variable. Similarly, Wolff et al (2017) also found variable emission for DH Tau B.…”
Section: How Common Is Paβ Emission?mentioning
confidence: 82%
“…Figure 9 compares the spectral energy distribution (SED) of GQ Lup B to the 2400 K, log g=4.0 BT-Settl model (Allard et al 2011). The temperature and surface gravity are chosen to be consistent with previous estimates (e.g., Marois et al 2007;McElwain et al 2007;Lavigne et al 2009). The model is normalized at K to minimize the effects from dust emission and extinction.…”
Section: Geometry Of the Systemmentioning
confidence: 99%
“…The data were reduced with the OSIRIS data reduction pipeline (DRP), 6 following the procedure described in McElwain et al (2007). We used the default 7 pixel (0.…”
Section: Spectroscopy: Integral Fieldmentioning
confidence: 99%